Protection of Strawberry Plants against Charcoal Rot Disease (Macrophomina phaseolina) Induced by Azospirillum brasilense - Viejobueno, Josefina (2021)
Some Plant Growth-Promoting Rhizobacteria (PGPR) can induce protection against pathogens, increasing plant tolerance to various diseases. This so-called biocontrol activity is replac-ing harmful practices in agriculture caused by the use of agrochemicals. Azospirillum brasilense is one of the PGPR already effectively used as a resistance inducer in several crops. The aim of this study was to evaluate the protective effect of PGPR A. brasilense strains isolated from strawberry and petunia plants (REC3, 2A1, 2A2, and 2E1) against the fungal pathogen Macrophomina phaseolina, which is the causal agent of the strawberry charcoal rot disease. In vitro antagonism assays and enzymatic tests on Petri dishes revealed no direct inhibition on M. phaseolina growth by any of the A. brasilense strains. However, strawberry plants treated with REC3 and 2A1 strains increased callose and lignin deposition and stomatal closure compared to untreated plants. In addition, treatments with either bacterial strains induced a defense response in strawberry plants against virulent isolates of M. phaseolina evidenced by an increased tolerance to the charcoal rot disease. These results suggest that A. brasilense REC3 and 2A1 strains can be used for the activation of innate immunity in strawberry plants as a strategy for managing charcoal rot in a sustainable and environmentally friendly way.